2005
DOI: 10.37855/jah.2005.v07i01.01
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and anti-ethylene treatment effects on cut 'First Red' rose.

Abstract: Studies were conducted to determine the effects of ethylene and anti-ethylene treatments on postharvest life of cut 'First Red' rose flowers. Effects of exogenous ethylene at 1, 10 and 100 µl l-1 for 48 h at 22 °C on cut 'First Red' rose flowers were investigated. Ethylene at different concentrations reduced postharvest life, with 100 µl l-1 having the greatest effect. Ethylene production measurements suggested that 'First Red' rose is climacteric during senescence. Pre-treatment of 'First Red' rose flowers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
(24 reference statements)
3
12
0
Order By: Relevance
“…3), STS did not affect water uptake or change in rose fresh weight (data not presented). Chamani et al (2005) found that 'First Red' vase life was extended with a 0.5 mM STS application but not 1-MCP treatment, which is consistent with the results for 'First Red' and the other five cultivars tested in this study where 1-MCP did not significantly improve vase life (Table 2). 1-MCP applied either as a fumigation or via sachets prevented a decrease in vase life from exogenous ethylene in one of three cultivars studied by Macnish et al (2010).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…3), STS did not affect water uptake or change in rose fresh weight (data not presented). Chamani et al (2005) found that 'First Red' vase life was extended with a 0.5 mM STS application but not 1-MCP treatment, which is consistent with the results for 'First Red' and the other five cultivars tested in this study where 1-MCP did not significantly improve vase life (Table 2). 1-MCP applied either as a fumigation or via sachets prevented a decrease in vase life from exogenous ethylene in one of three cultivars studied by Macnish et al (2010).…”
Section: Resultssupporting
confidence: 90%
“…Philosoph-Hadas et al (2005) found that treating stems with 0.4 mLÁL -1 1-MCP for 4 h increased vase life for rose cultivars Pink Tango, Jazz, Frisco, and Golden Gate compared with ethylene-exposed control stems, and Macnish et al (2010) found that various types of 1-MCP treatment prevented the negative effects of exogenous ethylene. However, Chamani et al (2005) found that treating stems with 1 mLÁL -1 1-MCP for 2 h did not improve vase life in 'First Red'. The effects of ethylene and antiethylene agents on water uptake are also not known.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This therefore suggests that early senescence and wilting is correlated to level of ethylene sensitivity. The results of ethylene sensitivity are in agreement with studies carried out on Dendrobium 'Khao Sanan' (Lerslerwong and Ketsa, 2008), mini Phalaenopsis (Sun et al, 2009), Oncidium 'Gower Ramsey' (Huang and Paull, 2009) and cut roses (Chamani et al, 2005). The weight losses in the cut orchids such as D. 'Darren Glory' and D. 'Shavin White' were higher than the others (Figure 1) and this could be related to the level of ethylene sensitivity.…”
Section: Discussionsupporting
confidence: 88%
“…The postharvest disorders in cut rose flowers are a major limitation in their ornamental value (Rihn et al, 2014). In order to prolong vase life of cut flowers, many previous studies have been conducted to reduce ethylene damage using various ethylene inhibitors, such as nitric oxide, silver thiosulfate (STS), and 1-methylcyclopropene (1-MCP), which repressed the transcript levels of ethylene biosynthesis and receptor genes (Chamani et al, 2005;Liao et al, 2013;Ichimura and Niki, 2014). Similarly, the bacteria-induced xylem blockage was prevented by using various chemical compounds containing silver ions that have antimicrobial activity to inhibit the growth of microorganism (Ichimura et al, 2008;Cumbal and Alma, 2016).…”
Section: Introductionmentioning
confidence: 99%